(3CSGSjGJ GdQjGVI ddJLGQjjf (B((3c(B1) ((3L(B2) /s - (3GdefUhQj(B;(3YR, YGOd YHO GdMejO (B;(3YeGQ, efi eMeO CMeO (B;(3YHO GdHGQj, eMeO hMjO, eMeO Jhajbs ((3GdbGgQI (B: s (3cdjI GdJLGQI(B, s)
(3GdaGFOI GdHSjWI h GdLedI , GdNUe h GdbjeI GdMGdjI , JShjI GdOjhf bUjQI GdCLd , GdbQhV bUjQI GdGLd h WQb SOGOgG , MSGHGJ GdJhajQ , GdLedI HGdaGFOI GdeQcHI , GdbjeI GdMGdjI h GdNUe , JShjI GdOjhf , GdbjeI GdMGdjI ddOaYGJ GdOGFeI , GdbjeI GdMGdjI ddOaYGJ GdeDbJI ,GdJcdaI GdQCSeGdjI , SOGO GdbQhV Ydi CbSGW eJSGhjI , SOGO GdbQhV Ydi CbSGW eJSGhjI NdGd aJQGJ GdbQV , Jbjje GdSfOGJ , SOGO GdbQhV GdSfhjI(B. s
(3edGMb (B284(3U(B. s
Keywords: (3GdOjhfs; (3GdSfOGJs; (3GdbQhVs